Florística vascular não arbórea de um fragmento de floresta estacional semidecidual no munícipio de Analândia - SP - Dinato, Daniela de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
(Nontrees Vascular Floristic of a fragment of Semideciduous Seasonal Forest in the municipality of Analândia - SP). The Rawistcher Park is located in Pedra Vermelha farm, in the city of Analândia, central-eastern region of São Paulo state, between the coordinates 22°06’53’’- 05’35’’S and 47°46’06’’- 45’14’’W. It is a Semideciduous Seasonal Forest fragment of about 80 ha that occurs on basaltic cuestas. This study aimed to conduct inventory of the nontrees (shrubs, ground herbs, epiphytes, climbers) vascular flora (including pteridophytes s.l.) of the area. Samplings were conducted from April 2012 to December 2013 using the method of traversal on trails. The nontrees flora of Rawistcher Park consists of 230 species belonging to 74 families, 89% angiosperms and 11% pteridophytes s.l. Asteraceae was the fanerogamic family with the highest number of species (17), followed by Piperaceae (13), Malvaceae (12), Rubiaceae (11), Cyperaceae (10) Solanaceae, Poaceae and Fabaceae (9), Bignoniaceae (8) and Orchidaceae (7). Polypodiaceae was the more representative family of Pteridophytes s.l. (5). Nontree flora represents above 53% of total know flora of Rawistcher Park. Regarding the life form, most are herbs (48%), followed by shrubs (23%), climbers (22%) and epiphytes (7%). Among all species, 19 are endemic to the Atlantic Forest and nine are non-native from brazilian flora. Six species of this survey are considered threatened or near threatened with extinction, according to the Red List of endangered species in the state of São Paulo. Compared with other floristic surveys, the results show a high local floristic richness and emphasize the heterogeneity and particularity of each forest fragment of São Paulo state, confirming the importance of its preservation

(Florística vascular não arbórea de um fragmento de Floresta Estacional Semidecidual no município de Analândia - SP). O Parque Rawistcher localiza-se na Fazenda Pedra Vermelha, no município de Analândia, região centro-leste do Estado de São Paulo, entre as coordenadas 22°06’53’’- 05’35’’S e 47°46’06’’- 45’14’’W. Trata-se de um fragmento de cerca de 80 ha de Floresta Estacional Semidecidual que ocorre sobre cuestas basálticas. O presente trabalho teve como objetivo principal realizar inventário da flora vascular (incluindo pteridófitas s.l.) não arbórea (arbustos, ervas terrestres, epífitas, trepadeiras) da área. Foram realizadas coletas de abril de 2012 a dezembro de 2013, utilizando-se o método de caminhamento em trilhas. A flora não arbórea do Parque Rawistcher é constituída por 230 espécies, distribuídas em 74 famílias, sendo 89% angiospermas e 11% pteridófitas s.l. Asteraceae foi a família fanerogâmica com maior número de espécies (17), seguida de Piperaceae (13), Malvaceae (12), Rubiaceae (11), Cyperaceae (10) Solanaceae, Fabaceae e Poaceae (9), Bignoniaceae (8) e Orchidaceae (7). Polypodiaceae foi a família de pteridófita s.l. mais representativa (5). A flora não arbórea constitui cerca de 53% da flora amostrada total do Parque Rawistcher. Em relação à forma de vida, a maioria são ervas terrestres (48%), seguidas de arbustos (23%), trepadeiras (22%) e epífitas (7%). Do total de espécies, 19 são endêmicas da Mata Atlântica e nove não são nativas da flora brasileira. Seis espécies do presente levantamento são consideradas ameaçadas ou quase ameaçadas de extinção, segundo o Livro Vermelho das espécies vegetais ameaçadas do Estado de São Paulo. Em comparação com outros levantamentos florísticos, os resultados mostram uma elevada riqueza florística local e ressaltam a heterogeneidade e particularidade de cada fragmento florestal do Estado, confirmando a importância..
Keywords: Plant ecology; Ecologia vegetal; Cuesta basáltica; Paisagens fragmentadas; Sistema vascular de plantas; Plantas; Pteridofita; Mata Atlântica